ISOLATION AND IDENTIFICATION OF BACTERIOCIN PRODUCING MICROBES USING BIOCHEMICAL AND MOLECULAR TOOLS AND ANALYSIS OF ITS BIOPRESERVATION POTENTIAL - Nandan, Parmar Keshri; Nagar, Anshita (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Food safety is a matter of utmost importance in developing countries as well as in developed countries, so keeping this in mind this research work deals with the identification and characterization of bacteriocin producing microbes by using biochemical and molecular characterization. This study has also covered the biopreservation potential of bacteriocin produced by these microbes against sapodilla, tomato and banana as well.Methods: For the purpose of sample collection and isolation, samples of milk, curd and gangajal water were taken and bacteriocin producing microbes were isolated by using serial dilution method. Screening of bacteriocin producing microbe was done by antibacterial sensitivity test using agar well diffusion method against Bacillus amyloliquefaciens, Escherichia Coli, Staphylococcus aureus and Pseudomonas aeruginosa by determining their zone of inhibition. Biochemical characterization was done by using different tests, such as, catalase test, mannitol test, citrate test, gelatin test, maltose test, indole test, urease test, lactose test etc. Molecular characterization was done by using 16S rRNA gene sequencing. Preservative action of bacteriocin was observed on fruits that comprise sapodilla, tomato and banana by spraying bacteriocin on them and analyzing their activities shows for at least 10 days. Results: Microbes were found to be Enterococcus faecalis (Accession number KX011874) and Bacillus cereus (Accession number KX011875). Periodic observatory studies reflect that using bacteriocin, banana can be preserved for nearly 6-7 days while sapodilla for 8-9 days and tomato for 9-10 days. Conclusion: From present study we would like to conclude that bacteriocins produced by microbes which is found in milk or curd can also be used as biopreservatives for these defined fruits that is sapodilla, tomato and banana. Keywords: Bacteriocin, Biopreservation, 16S rRNA analysis.